Visual Semiotics of Instagram Advertising Posters: A Grammar of Visual Design Analysis of Indonesian Soda Brands - Juvelman Harefa; Daniel Sbastian (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Despite the growing use of Instagram advertising, comparative visual semiotic studies examining how competing soda brands construct brand identity remain limited. This study analyzes how visual elements in soda drink advertising posters shape meaning and brand image through four aspects of Kress and van Leeuwen's (2006) Grammar of Visual Design: composition, modality, represented participants, and interactive participants. A descriptive qualitative approach was applied to eight official Instagram posters from the four most popular soda brands in Indonesia (Coca-Cola, Fanta, Sprite, and BIG Cola) based on the 2025 Top Brand Award. While all four brands share high visual modality and product-centric composition, they differentiate through distinct coding orientations: Coca-Cola and Sprite employ naturalistic realism to convey authenticity and purity, Fanta adopts a sensory orientation with stylized visuals to express youthful energy, and BIG Cola blends naturalistic detail with sensory boldness. All brands predominantly use the offer image, positioning the audience as observers. Critically, BIG Cola uniquely deploys a demand image through the direct gaze of football stars, creating a parasocial connection absent in the market leaders. This study demonstrates how brands in the same product category construct distinctive multimodal identities on Instagram, and how a challenger brand uses the demand image to disrupt convention. The findings provide practical insights for marketers in designing visual brand identities and contribute to multimodal advertising research in digital communication.